Réponses

2013-12-01T14:19:23+01:00
Tu développe :
6x-3-4+4x<2x+6
10x-7<2x+6
Tu passes le 2x+6 de l'autre côté par soustraction :
8x-13<0
Alors 8x<13
Et x<13/8
Voilà j'espère que ça t'aide!
2013-12-01T14:24:45+01:00
3(2x-1)-4(1-x) ≤ 2(x+3)
6x-3-4+4x 
≤ 2x+6
10x-7 ≤ 2x+6
8x ≤ 13
x ≤ 13/8

((5x-2)/8)-((1-x)/5) > (3(x-3))/10
((25x-10)/40)-((8-8x)/40) > (12x-36)/40
((25x-10)-(8-8x))/40 > (12x-36)/40
((33x-18)/40)-((12x-36)/40) > 0
((33x-18)-(12x-36))/40 > 0
(21x+18)/40 > 0
21x+18 > 
21x > -18
x > -18/21
x > -6/7